Le genre masculin n'est pas neutre - Alonzo, Philippe; Silvera, Rachel (Travail, genre et sociétés, 2000)
Keywords: approches et analyses; discipline; inégalités; patriarcat; projet charge mentale; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Le siècle dans la tourmente du féminisme - Daigle, Johanne (Globe : revue internationale d’études québécoises, 2000)
L’empreinte du féminisme sur le XXe siècle québécois est indélébile. De l’aube au crépuscule du siècle, la « question des femmes » a coloré les grands débats, imprégné les luttes socio-politiques et laissé sa marque sur les systèmes de lois, les institutions, l’organisation du travail et les modes de vie. Cet article veut montrer comment, dans une perspective historique, la « question des femmes » — ainsi posée par les élites masculines — fut pressentie comme l’une des grandes interrogations de ce siècle et comment les changements survenus dans la reconfiguration des rapports entre hommes et femmes — des identités sexuelles aux modèles qui les supportent — restent au coeur des enjeux d’une société.
https://www.erudit.org/en/journals/globe/2000-v3-n2-globe1497493/1000582ar/
Keywords: 1900-1999; EDI; amériques; approches et analyses; conflit; cours; discipline; discours dominant; droits des femmes*; fem1000; histoire; histoire et politique; inégalités; militance; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail; épistémologie

Mariage et classes sociales: les Montréalais francophones entre les deux Guerres - Girard, Denise (Institut québécois de recherche sur la culture, Presses de l'Université Laval, 2000)
Un éclairage inédit sur une population urbaine à un moment charnière de son évolution: celle des Montréalais francophones des décennies 1920 et 1930. Une période où la population d'ascendance française devient majoritaire à Montréal
Keywords: 1900-1999; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; his4523; histoire; mariage; montréal; patriarcat; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Columbia University Press, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Section: xxii, 156 p. ; 24 cm.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Au sujet des corps, des techniques et des féminismes dans L'invention du naturel: les sciences et la fabrication du féminin et du masculin - Oudshoorn, Nelly (L'invention du naturel: les sciences et la fabrication du féminin et du masculin, 2000)
Section: 227 pages ; 21 cm
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; cours; discipline; essentialisme; europe; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques